2021
DOI: 10.3389/fmed.2021.708140
|View full text |Cite
|
Sign up to set email alerts
|

Role of Th22 Cells in Human Viral Diseases

Abstract: Naive CD4+ T cells can differentiate into different cell subsets after receiving antigen stimulation, which secrete corresponding characteristic cytokines and thereby exert biological effects in various diseases. Th22 cells, a novel subset of CD4+ T cells, are different from Th1, Th2, Th17, and Treg cell subsets, which have been discovered in recent years. They can express CCR4, CCR6, and CCR10 molecules and secrete IL-22, IL-13, and TNF-α. They are not able to secrete IL-17, IL-4, and interferon-γ (IFN-γ). IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 75 publications
0
20
0
9
Order By: Relevance
“…The increased Th17 proportions and IL-22 were observed in cases with headache, hyperinflammation, respiratory system dysfunction, and ARDS ( 163 , 197 ). Other studies indicated that IL-22 levels are negatively correlated with the Th22 levels ( 188 , 198 ). Functional assays revealed that both peripheral blood mononuclear cells (PBMCs) and a human bronchial epithelial cell line (16HBE) can produce IL-22 ( 188 ).…”
Section: Cytokine Secretion Induced By Sars-cov-2 Infectionmentioning
confidence: 94%
See 2 more Smart Citations
“…The increased Th17 proportions and IL-22 were observed in cases with headache, hyperinflammation, respiratory system dysfunction, and ARDS ( 163 , 197 ). Other studies indicated that IL-22 levels are negatively correlated with the Th22 levels ( 188 , 198 ). Functional assays revealed that both peripheral blood mononuclear cells (PBMCs) and a human bronchial epithelial cell line (16HBE) can produce IL-22 ( 188 ).…”
Section: Cytokine Secretion Induced By Sars-cov-2 Infectionmentioning
confidence: 94%
“…Other studies indicated that IL-22 levels are negatively correlated with the Th22 levels ( 188 , 198 ). Functional assays revealed that both peripheral blood mononuclear cells (PBMCs) and a human bronchial epithelial cell line (16HBE) can produce IL-22 ( 188 ). This suggests that IL-22 could be expressed differently in peripheral blood and tissues.…”
Section: Cytokine Secretion Induced By Sars-cov-2 Infectionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although IL-22 was primarily discovered that IL-22 was produced by Th1 and natural killer (NK) cells ( 25 ), IL-22 was usually viewed as a Th17 cytokine ( 26 , 27 ) until the identification of Th22 cells ( 8 11 ). They were discovered as a new subset that only secreted IL-22, and barely produced IFN-γ, IL-4, or IL-17 ( 15 , 20 ). Duhen estimated that about a half of IL-22 producing CD4+ memory T cells from healthy human peripheral blood secreted only IL-22, whereas around 30% and 13% separately co-expressed IFN-γ and IL-17, separately, with nearly 6% producing all three ( 9 ).…”
Section: Characterization and Differentiation Of Th22 Cellsmentioning
confidence: 99%
“…Type 22 T helper (Th22) cells are characterized by synthesis of IL-22 (and also IL-13 and TNF- α ) but not IL-17 or IFN- γ [ 27 ]. These lymphocytes, in addition to their role in host defense against different infectious agents and homeostasis, may also exert a proinflammatory effect, participating in the pathogenesis of different immune-mediated conditions such as psoriasis, asthma, inflammatory bowel disease, and systemic sclerosis as well as in viral infections [ 27 , 28 ]. In addition, Th22 and IL-22 seem to have a relevant role in the pathogenesis of RA [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%